Students’ Strategies to Overcome Public Speaking Anxiety - Martiningsih, Indah; Susilawati, Endang; Rezeki , Yanti Sri (Inspiring: English Education Journal, 2024)
Public speaking anxiety (PSA) is a problem that often occurs in the language learning process therefore this study was conducted to find the strategies students use to overcome the public speaking anxiety they experience using the theory developed by Kondo and Ying Ling (2004). This study used a quantitative method with a descriptive approach. The participants of this research were 40 students of the English education study program of FKIP at Universitas Tanjungpura. The results showed that relaxation strategy is the most chosen strategy by students as the strategy they use to overcome their public speaking anxiety with the percentage 83.2%, followed by the preparation strategy as the second strategy with the percentage 80.1%, then third is peer seeking strategy chosen by 80% students and the last is the positive thinking strategy as much as 78.2%. The limitations of this study are as follows: it does not provide data on students' levels of anxiety, lacks diversity in the tools used, focuses solely on students who have completed the course, and does not explore strategies beyond those suggested in the questionnaire.